Investigating sex differences in astrocytes and the adaptive immune system in the APP/PS1 AD mouse model and in Alzheimer's disease patients - Lambe, Jessica Beth (Trinity College Dublin. School of Medicine. Discipline of Physiology, 2026)
Alzheimer’s disease (AD) is the most common neurodegenerative disease. The prevalence of this disease amongst the sexes is heterogenous with females making up 2/3 of AD patients. The pathohistological hallmarks of the disease are the build-up of extracellular A plaque, intracellular neurofibrillary tau tangles and neuroinflammation in the brain. In more recent years, it has been reported that microglia from females and males present differences in their morphology, metabolism, phagocytic ability and iron retention. It has been shown that the release of pro-inflammatory cytokines TNF-, IL-1, and complement component 1q (C1q) by microglia (TIC factors) are required for astrocytes to become reactive, indicating an important interplay between the glial cells. The role of the adaptive immune system in AD has become an area of research more recently as T lymphocytes from the adaptive immune system have been shown to be implicated in AD pathogenesis. Although their role in the disease and potential sexual dimorphisms in T cell subsets is not fully understood. The general hypothesis of my PhD project is that alterations in abundance and/or phenotype of T cells and/or astrocytes differ in males and females in response to AD pathology. The aim of my project is to investigate potential sex differences in astrocytes and in CD4+ and CD8+ T cells. To do so, flow cytometry was performed on secondary lymphoid organs in APPswe/PSEN1dE9 mice (model of Alzheimer’s disease (AD) and cerebral amyloidoisis) once pathology was well established (16-17 months). The secondary lymphoid organs (lymph nodes and spleen) contain mature T and B cells and become activated by encountering antigens and initiate an adaptive immune response. Immunofluorescence on brain sections was used for the evaluation of astrogliosis. In this study, significant changes in CD8+ T cell populations were observed in lymph nodes (IFN-γ, TNF- and IL-17) which did not occur in T cells isolated from spleens. There was also a significant decrease in regulatory T cells located in the brain but not in the lymph nodes or spleen. In relation to astrocyte response, GFAP expression is significantly increased in the CA3 of the hippocampus in female APP/PS1 mice compared to male APP/PS1 mice. This indicates that the adaptive immune system, specifically T cells and astrocytes are altered in AD pathology in the APP/PS1 model. Additionally, peripheral blood mononuclear cells (PBMCs) and cerebrospinal fluid (CSF) were collected from AD and non-AD patients to investigate alterations in T cell phenotypes and cytokine response. Meso-scale discovery analysis revealed significant alterations in proteins secreted in the CSF but not PBMCs of AD patients (MIP1 and IFN-γ). The effect of sex was also observed in the CSF with specific protein secretions altered in only male or female AD patients alone (IL-1R in males and IL-6 in females). Furthermore, induced pluripotent stem cells (iPSC) were utilised to generate cortical astrocytes. Astrocytes were treated with male and female non-AD and AD patients’ CSF and conditioned media from PBMCs to elucidate the potential sex differences and interplay between the immune system and astrocytes. Interestingly, treatment with AD CSF but not PBMCs resulted in significant decrease in astrocyte protein secretion confirmed by ELISA (CXCL10). In conclusion, CSF is key to further elucidating the pathogenesis of AD along with the inclusion of both male and females as the response to pathology is not uniform between the sexes. Future studies could utilise this approach in identifying sex specific differences in both the adaptive immune system as well as astrocytes to prevent the characteristic neuroinflammation and neurodegeneration in AD with pharmaceutical interventions.
APPROVED
Keywords: Alzheimer's; astrocytes; T cells